Pengaruh Parenting Islami terhadap Karakter Disiplin Anak Usia Dini - Masganti Sitorus; Eka Damayanti Hasibuan; Diana Siregar; Yasmin Fajri (Inovasi Pendidikan dan Anak Usia Dini, 2026)
This study aims to explore in depth the impact of Islamic parenting on the development of disciplinary character in early childhood. Conceptually, parenting in Islam is understood as a child-rearing method based on Islamic principles, emphasizing values of role modeling, love, responsibility, and moral development from an early age. Through this approach, parents serve as the first and foremost educators in instilling the values of discipline reflected in children’s daily behavior, both within the family and in social interactions. This research analyzes various ways Islamic parenting is applied in daily activities, including the habit of performing prayers on time, managing schedules for study and play, and implementing educational consequences in accordance with Islamic principles. The findings reveal that the consistent application of Islamic parenting patterns, combined with effective communication between parents and children, has a positive effect on the development of children’s disciplinary character. Children raised under Islamic parenting tend to have an awareness of obeying rules, valuing time, and taking responsibility for their duties and obligations. Conversely, the study also identifies challenges stemming from parents’ limited understanding of Islamic parenting concepts, as well as external environmental influences such as digital media and peer interactions that are not always aligned with Islamic values. Therefore, efforts are needed to improve literacy regarding Islamic parenting through educational activities involving early childhood education institutions, religious study groups, and parent communities. In general, the findings of this study highlight the importance of collaboration among families, schools, and communities in consistently applying Islamic parenting principles to foster children’s disciplinary character from an early age in accordance with Islamic teachings.